Combating Terrorism: The Role of Millennials in Addressing and Preventing Terrorism - Slamet Pribadi (International Journal of Social Service and Research, 2023)
As the wheel of life never stops turning, the same way the fight against terrorism must be carried out. As a country based on Pancasila which inspires divinity and humanity, we as the people of Indonesia must agree and work together to prevent and fight terrorism. All elements and state apparatus have tried to fight terrorism, and from all of them it is the youth or millennial generation as future leaders who are able to continue this struggle. It is not a strange thing that currently the movement of terrorism groups still exists and continues to move, they are not only planning a new pattern of attacks at a time and place at this time, but they do not forget to look for the next generation of their movement, new seeds that later implanted a radical thought and seemed heretical. Therefore, the author hopes that through this paper, it can be an information and also a reminder for the younger generation, that the era of their struggle in responding to and preventing terrorism has just begun, and therefore their participation must continue to exist in supporting the eradication of terrorism